Age-related changes in liver metabolism and antioxidant capacity of laying hens - Y.F. Gu (Elsevier, 2021)
ABSTRACT: This study aimed to investigate the age-related changes of hepatic metabolism and antioxidant capacity of laying hens at 3 different ages. A total of 192 Hy-line Brown laying hens were assigned into 3 groups: 1) 195-day-old (D195 group); 2) 340-day-old (D340 group); 3) 525-day-old (D525 group). Each group replicated 8 times with 8 hens at the same age. Higher activity of aspartate aminotransferase and lower contents of total protein and globulin were observed in the serum of 525-day-old hens in comparison with their 195-day-old counterparts (P < 0.05). The 525-day-old hens accumulated higher contents of total cholesterol and triglyceride in the liver than 195-day-old birds. Additionally, compared with hens from D195 or D340 group, 525-day-old birds exhibited a lower circulating estradiol level (P < 0.05). For antioxidant capacity, birds in the D525 group showed a higher malondialdehyde concentration in both serum and liver as compared with D195 or D340 group (P < 0.05). The 525-day-old hens also exhibited lower glutathione peroxidase activities in both serum and liver when compared with 195-day-old birds (P < 0.05). Simultaneously, there was a decline of hepatic superoxide dismutase activity in the D525 group in comparison with D195 group (P < 0.05). Compared with 195-day-old counterparts, 340-day-old birds upregulated the mRNA abundance of nuclear factor erythroid-2 related factor 2 and glutathione peroxidase 1 in the liver (P < 0.05). In contrast, hens from D525 group showed the downregulation of hepatic nuclear factor erythroid-2 related factor 2, NAD(P)H quinone dehydrogenase 1, and superoxide dismutase 1 when compared with D340 group (P < 0.05). These results indicated that increasing age can adversely affect liver metabolism and function of laying hens.